2016
DOI: 10.3390/e18050167
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tsunami Bore Forces on a Coastal Bridge Using an Extreme Learning Machine

Abstract: This paper proposes a procedure to estimate tsunami wave forces on coastal bridges through a novel method based on Extreme Learning Machine (ELM) and laboratory experiments. This research included three water depths, ten wave heights, and four bridge models with a variety of girders providing a total of 120 cases. The research was designed and adapted to estimate tsunami bore forces including horizontal force, vertical uplift and overturning moment on a coastal bridge. The experiments were carried out on 1:40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The Confusion Matrix showed that the model correctly classified 232 instances of potential tsunamis and 37 cases of non-potential tsunamis out of 269 actual occurrences. However, 52 instances were falsely International Journal Software Engineering and Computer Science (IJSECS), 4 (1) 2024, [13][14][15][16][17][18][19][20][21][22][23] Classification of Potential Tsunami Disaster Due to Earthquakes in Indonesia Based on Machine Learning predicted as non-potential tsunamis and 77 instances were falsely predicted as potential tsunamis, indicating some misclassifications.…”
Section: Discussionmentioning
confidence: 99%
“…The Confusion Matrix showed that the model correctly classified 232 instances of potential tsunamis and 37 cases of non-potential tsunamis out of 269 actual occurrences. However, 52 instances were falsely International Journal Software Engineering and Computer Science (IJSECS), 4 (1) 2024, [13][14][15][16][17][18][19][20][21][22][23] Classification of Potential Tsunami Disaster Due to Earthquakes in Indonesia Based on Machine Learning predicted as non-potential tsunamis and 77 instances were falsely predicted as potential tsunamis, indicating some misclassifications.…”
Section: Discussionmentioning
confidence: 99%
“…Designing computational prediction models to predict future situations or gravity of the illness can assist to improve the quality of healthcare. Main benefits involve helping medical professionals to control their patients efficiently by offering a proper treatment plan; preventing hospitalization, a significant driver of expenses; and helping health scientists to design clinical trials by focusing on high risk individuals with heterogeneous features for disease-modifying health interventions [69]. The healthcare domain is growing quickly, with an expanding range of treatments and diagnostics fueled by developments in immunology, genetics, and biology features.…”
Section: Discussion and Challengesmentioning
confidence: 99%
“…The Editor-in-Chief has retracted this article (Toghroli et al 2018) because validity of the content of this article cannot be verified. This article showed evidence of substantial text overlap (most notably with the articles cited Cojbasic et al 2016;Mazinani et al 2016;Mohammadian et al 2016;Mansourvar et al 2015) and authorship manipulation. Meldi Suhatril, Zainah Ibrahim, Maryam Safa, Mahdi Shariati and Shahaboddin Shamshirband do not agree to this retraction.…”
mentioning
confidence: 87%